Analisis Determinan Kepuasan Konsumen Produk Kecantikan Di Aplikasi Sociolla - Adinda Lita Rachman; Joel Faruk Sofyan (Politeknik Kampar, 2023)
With increasingly intense competition in e-commerce, companies engaged in this business must be able to provide excellent service quality to consumers to maintain customer loyalty, so that customers are willing to make more transactions with these companies. This research examines the effects of service quality, perceived ease of use, perceived value, and customer experience on customer satisfaction in the Sociolla application. This study used primary data collected through an online survey with questionnaires distributed to 125 selected respondents in June - July 2023. The research criteria are consumers aged above 17 years who have made at least one purchase of skincare, makeup, and bodycare products from Sociolla within the last 3 months and domiciled in Jakarta and Tangerang. The analysis method used is multiple linear regression as an inferential tool, this research found that service quality, perceived ease of use, perceived value, and customer experience partially have positive effects and simultaneously affect customer satisfaction.